An Analysis of Theme and Rheme of The Text in a Book of Physics for grade VII of Junior High School - Yuria Kasmita; Iis Sujarwati (Yayasan Karinosseff Muda Indonesia, 2022)
Theme and rheme as the main attention which will be discussed in a text and the theme will be supported by the rheme. Rheme is supporting sentences which will explain the theme more detail, so the readers can get the messages deeply which will be conveyed by the writer. This study aims to analyse the theme and rheme in bilingual book, a Book of Physics for grade VII of Junior High School. The objective of this study to know the theme and rheme from source language into target language, whether the theme and the rheme has preserved or has changed. The object in this research is a book, a Book of Physics for grade VII of Junior High School. We will analyse some texts or passages in this which are written in English and Indonesian. This research is quantitative research which will be analyzed the text descriptively based on their textual equivalence: thematic structure